Resilience of Family of Police Brimob Members Serving in Conflict Area in the Perspective of National Defense - Roma Megawanty; Hanita Margaretha; Maria Puspitasari (Budapest International Research and Critics University, 2021)
This paper discusses the potential vulnerability of families to members of the Police Mobile Brigade assigned to conflict areas. This study uses a qualitative methodology. The theories and concepts used are the theory of national resilience and the theory of family resilience. This study analyzes the development of a prosperous family as the smallest unit in society which has a very important role in national development. If the family has high resilience, then family welfare can be achieved, which in turn will produce quality human resources for national development. In addition, there is no scientific information available regarding programs aimed at increasing family resilience.